The Effect of Physalis angulata L. Administration on Gene Expressions Related to Lung Fibrosis Resolution in Mice-Induced Bleomycin - Imaduddin UK; Berbudi A; Rohmawaty E (Dove Medical Press, 2024)
Ummul Khair Imaduddin,1 Afiat Berbudi,2,* Enny Rohmawaty3,* 1Graduate School of Master Program in Anti Aging and Aesthetic Medicine, Faculty of Medicine, Universitas Padjadjaran, Bandung, West Java, Indonesia; 2Parasitology Division, Department of Biomedical Sciences, Faculty of Medicine, Universitas Padjadjaran, Bandung, West Java, Indonesia; 3Pharmacology & Therapy Division, Departement of Biomedical Sciences, Faculty of Medicine, Universitas Padjadjaran, Bandung, West Java, Indonesia*These authors contributed equally to this workCorrespondence: Enny Rohmawaty, Pharmacology & Therapy Division, Department of Biomedical Sciences, Faculty of Medicine, Universitas Padjadjaran, Jl. Raya Bandung-Sumedang, KM.21, Hegarmanah, Kec. Jatinangor, Kabupaten Sumedang, Bandung, West Java, 45363, Indonesia, Email e.rohmawaty@unpad.ac.idPurpose: To explore the potential therapeutic effects of Physalis angulata L. (Ciplukan) extract on lung fibrosis resolution in a Bleomycin-induced mouse model, researchers conducted a comprehensive study. The study focused on key genes associated with fibrosis progression, including Nox4, Mmp8, Klf4, and FAS, and assessed their mRNA expression levels following the administration of Ciplukan extract.Methods: A Bleomycin-induced mice model was divided into seven groups to investigate the effects of ciplukan extract on fibrosis-related gene expressions. Mice were induced with subcutaneously injected Bleomycin to generate lung fibrosis and given different doses of the Ciplukan extract for four weeks. Lung fibrosis mRNA expression was analyzed by semi-quantitative PCR for Nox4, Klf4, Mmp8, and FAS.Results: The administration of ciplukan extract resulted in a significant decrease in mRNA expression of Nox4 with p-value=0.000, Mmp8 with p-value =0.002, and Klf4 with p-value =0.007, indicating potential antifibrotic effects. However, FAS expression remained unchanged (p-value=0.127).Conclusion: Ciplukan extract exhibited promising effects on fibrosis-related gene expressions, particularly Nox4, Mmp8, and Klf4. This study suggests that the extract has the potential to intervene in fibrosis progression, offering a potential avenue for therapeutic strategies.Keywords: ciplukan, FAS, Klf4, lung fibrosis, Mmp8, Nox4, pulmonary fibrosis, Physalis angulata L